ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI MELON DI DESA TUNGKU JAYA KECAMATAN SOSOH BUAY RAYAP KABUPATEN OKU (JASEP, 2018)
This study aims to analyze the income and feasibility of melon farming in Desa Tungku Jaya, Kecamatan Sosoh Buay, Kabupaten Ogan Komering Ulu. This research was conducted in Desa Tungku Jaya, Kecamatan Sosoh Buay, Kabupaten Ogan Komering Ulu. The method used in this research is survey method. Data were obtained by interview and face-to-face interview with respondent using questionnaire as data collecting tool. The sampling method used is the saturated sampling method. The population in this research is melon farming farmers with a total of 20 farmers. Due to the amount of less than 30 then the entire population is taken as all samples. The results of research conducted, it can be concluded that the production income generated by melon farmers is Rp. 33,676,129 and the feasibility of melon farming in Desa Tungku Jaya, Kecamatan Sosoh Buay, Kabupaten Ogan Komering Ulu is 2,022.